Pelenggaraan Bazar Murah Untuk Penguatan Pemasaran UMKM Di Kota Metro Lampung - Desmon, Desmon (ANDASIH Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity aims to strengthen the marketing capacity of MSMEs in Metro City Lampung through the organization of a low-cost bazaar designed as a community-based intervention and practical learning medium for students. A participatory approach was used by involving MSMEs, students, and activity partners in all stages of planning, implementation, and evaluation. Data were collected through participatory observation, semi-structured interviews, and visitor satisfaction surveys. The results of the activity show that the bazaar was able to increase the visibility of MSME products and provide a meaningful entrepreneurial experience for students. These findings reinforce the literature that emphasizes the effectiveness of community-based marketing interventions on the competitiveness of MSMEs. This activity is recommended to be replicated with a more measurable evaluation design.